Redes de distribución con transbordo como elemento de resiliencia empresarial: una revisión sistemática - Muyulema-Allaica, Juan-Carlos; Rodríguez-Balón, Jean-Carlos (Revista Científica, 2023)
Distribution networks with transshipment are an important factor for moving of products and inputs, promoting and improving the reduction of transportation costs regarding distribution problems. This paper focuses on answering the following question based on a systematic literature review (SLR): How do transshipment distribution networks influence the reduction of transportation costs in resilient companies? A review and an estimation of preliminary research was carried out for a period of five years, operating the search engines of SciencieDirect, Redalyc, Dialnet, Scielo, and SpringerLink. The studies were selected based on a set of inclusion and exclusion criteria. It was highlighted that distribution networks with transshipment have a direct relationship with companies and aim for their well-being. On the other hand, the importance and theoretical bases of distribution networks were observed. The SLR collected clear and precise data for the study, which contributed to the understanding of the direct relationship between distribution networks and companies. The importance of logistics with transshipment in business resilience was established, which includes three basic aspects (recovery, vulnerability, and adaptation) with respect to the conditions of distribution as a contribution to sustainable development.